PENGARUH TARIF DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD RAA SOEWONDO PATI - Kusuma, Edi Wijaya; Suryoko, Sri; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Decrease the number of hospitalized patients suspected to be caused by the increase in service rates hospitals Soewondo Starch RAA. Aside from the issue of health care levy rate increase is also due to the performance indicators of hospitals RAA. Starch Soewondo weakened. So it is necessary to do research on